Accuracy of the SRK/T Formula in Pediatric Cataract Surgery - Irfani I; Wahyu T; Oktarima P; Caesarya S; Sari M; Karfiati F (Clinical Optometry, 2023)
Irawati Irfani,1,2 Tri Wahyu,1 Primawita Oktarima,1,2 Sesy Caesarya,1,2 Maya Sari,1,2 Feti Karfiati1,2 1Department of Ophthalmology, Faculty of Medicine Universitas Padjadjaran, Bandung, West Java, Indonesia; 2Pediatric Ophthalmology & Strabismus Division, Cicendo National Eye Hospital, Bandung, West Java, IndonesiaCorrespondence: Irawati Irfani, Email irawati.irfani@unpad.ac.idPurpose: Determining IOL power is an important step in achieving the desired postoperative refractive target, but this determination remains challenging, as currently the used formulas were developed using IOL power calculations derived from adults.Patients and Methods: This is a retrospective analytical study with the period of June 2018 to May 2019. All of the data were taken from medical records in referral tertiary eye hospital in Indonesia. All type of cataracts underwent uncomplicated surgeries and in-the-bag IOL implantation were included in this study, while aphakia, secondary IOL implantation, primary sulcus implantation, and history of ocular disorders were excluded. The data were analyzed using Wilcoxon sign-rank, paired t, and Kruskal–Wallis tests.Results: Sixty-seven patients (106 eyes) were found to meet the inclusion criteria, average age was 7.35 ± 4.61 years (1.00 to 17.00 years). Average targeted refraction was 1.69 ± 2.06 D (− 0.38–+6.99 D), and spherical equivalent (actual postoperative refraction) was − 0.90 ± 1.45 D (− 4.38 to +2.75 D). There was statistically significant difference between preoperative targeted refraction and actual postoperative refraction (p < 0.001). Mean absolute prediction error (APE) in general was 1.34 ± 1.18 D, 1.22 ± 0.88 D (in short eyes), 1.52 ± 1.37 D (in moderate eyes), and 0.69 ± 0.52 D (in long eyes) (p = 0.202). Mean APE in age group < 7 years old was 1.27 ± 1.18 D and ≥ 7 years-old was 1.42 ± 1.19 D (p = 0.429).Conclusion: SRK/T formula is fairly accurate in calculating IOL power in pediatric cataract surgery. Mean APE in this study was within the range of accurate mean APE in pediatric patients despite differentiated axial length and age.Keywords: absolute prediction error, SRK/T formula, pediatric cataract